COMPARATIVE EFFECTIVENESS OF PLATELET-RICH PLASMA, HYALURONIC ACID, AND CORTICOSTEROID INJECTIONS IN MODERATE KNEE OSTEOARTHRITIS (Asian Journal of Medical Research and Health Sciences, 2026)
Background:  Knee osteoarthritis is a common degenerative joint disorder causing pain, stiffness, and functional limitation in the elderly population. Intra-articular injections such as platelet-rich plasma (PRP), hyaluronic acid (HA), and corticosteroids are widely used for symptomatic management, but their comparative effectiveness remains a topic of ongoing research. Aim:  To compare the effectiveness of platelet-rich plasma, hyaluronic acid, and corticosteroid injections in patients with moderate knee osteoarthritis. Materials and Methods: This prospective observational study was conducted at Dindigul Medical College from April 2025 to September 2025 with a 6-month follow-up period. A total of 60 patients aged between 50 and 60 years with moderate knee osteoarthritis were included in the study. Patients were divided into three groups of 20 each: PRP group, hyaluronic acid group, and corticosteroid group. Clinical outcomes were assessed using pain and functional outcome measures during a follow-up period of six months. Results: The PRP group demonstrated the greatest improvement in pain relief and functional outcome scores at the end of six months. The hyaluronic acid group showed moderate improvement, while the corticosteroid group showed comparatively lesser sustained benefit. Overall clinical improvement was observed in the order of PRP > Hyaluronic acid > Corticosteroid. Conclusion: Platelet-rich plasma injections were found to be more effective than hyaluronic acid and corticosteroid injections in patients with moderate knee osteoarthritis over a six-month follow-up period. Hyaluronic acid also demonstrated better outcomes than corticosteroid injections, suggesting that PRP may be a superior treatment option for long-term symptomatic relief.